Tele-medicine : geriatric care at Khoo Teck Puat Hospital. - Oh, Zhi Jie. (2012)
As part of Khoo Teck Puat Hospital's (KTPH) Telemedicine project by its Geriatric Medicine department, a business process study was conducted. The conclusion is that a software system to handle the manual documentation process could greatly enhance the efficiency and reduce chances of human error. A software requirements study was conducted, and a software prototype was developed as a proof-of-concept.